Role of the pectoralis major myofascial flap in preventing pharyngocutaneous fistula following salvage laryngectomy. Issue 9 (8th August 2016) - Sharma, S; Chaukar, D A; Laskar, S G; Kapre, N; Deshmukh, A; Pai, P; Chaturvedi, P; D'Cruz, A
Abstract: Objective: This study aimed to assess the utility of onlay pectoralis major myofascial flap in preventing pharyngocutaneous fistula following salvage total laryngectomy. Methods: A retrospective analysis was performed of 172 patients who underwent salvage laryngectomy for recurrent carcinoma of the larynx or hypopharynx between 1999 and 2014. One hundred and ten patients underwent primary closure and 62 patients had pectoralis major myofascial flap onlay. Results: The overall pharyngocutaneous fistula rate was 43 per cent, and was similar in both groups (primary closure group, 43.6 per cent; onlay flap group, 41.9 per cent; p = 0.8). Fistulae in the onlay flap group healed faster: the median and mean fistula duration were 37 and 55 days, respectively, in the primary closure group and 20 and 25 days, respectively, in the onlay flap group ( p = 0.008). Conclusion: Use of an onlay pectoralis major myofascial flap did not decrease the pharyngocutaneous fistula rate, although fistula duration was shortened. A well-designed randomised-controlled trial is needed to establish parameters for its routine use in clinical practice.